2020
DOI: 10.3389/fgene.2020.595324
|View full text |Cite
|
Sign up to set email alerts
|

A Multi-Source Data Fusion Framework for Revealing the Regulatory Mechanism of Breast Cancer Immune Evasion

Abstract: For precision medicine, there is an enormous need to understand the immune evasion mechanism of tumor development, especially when tumor heterogeneity significantly affects the effect of immunotherapy. Recognizing the subtypes of breast cancer based on the immune-related genes helps to understand the immune escape pathways dominated by different subtypes, so as to implement effective treatment measures for different subtypes. For that, we used non-negative matrix factorization and consistent clustering algorit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 32 publications
(32 reference statements)
0
3
0
Order By: Relevance
“…Furthermore, the relationship between CNVs and gene expression is crucial for the prevention, diagnosis, and treatment of cancer (Shao et al 2019 ). CNV-caused genetic mutations may lead to the development of immune escape (Chen et al 2020 ). It has also been reported that copy number gains (CN gain) occur more frequently than copy number losses (CN loss) during epithelial-mesenchymal transition (EMT), and somatic CN gain activates gene expression by increasing gene dosage (Zhao et al 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the relationship between CNVs and gene expression is crucial for the prevention, diagnosis, and treatment of cancer (Shao et al 2019 ). CNV-caused genetic mutations may lead to the development of immune escape (Chen et al 2020 ). It has also been reported that copy number gains (CN gain) occur more frequently than copy number losses (CN loss) during epithelial-mesenchymal transition (EMT), and somatic CN gain activates gene expression by increasing gene dosage (Zhao et al 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…CNVs are an important form of genetic structural variation and are crucial for cancer diagnosis, prevention, and treatment. Furthermore, CNV-induced gene mutations may lead to immune escape ( 44 , 45 ). In our study, we observed a high CNV frequency in CAF markers and a correlation between CNV and marker expression, suggesting that CNV may affect CAF function and contribute to tumorigenesis.…”
Section: Discussionmentioning
confidence: 99%
“…ATAC-seq data have demonstrated that CDH1 is positively regulated by TFs such as NFATC2, XBP1, YY1AR, GTF2I, IRF2, and NF1, and variations in CDH1 expression are mainly caused by CNV. However, CNV and the mRNA level of PVRL2 are very weakly correlated, and high expression of PVRL2 may also be induced by increases in TFs including FOXP3, GTF2I, YY1, NR3C1, SP1, TFAP2A, AR, ESR1, PAX5, and TP53 ( 80 ). This evidence indicates that ITH in breast cancer is boosted by the combined action of tumor cells and immune cells in the TME.…”
Section: Single-cell Sequencing In Cancer: Lessons Learnedmentioning
confidence: 99%